The Technology Development and Management of Smart Manufacturing System: A Review On Theoretical and Technological Perspectives - Al-Amin, Md.; Hossain, Md. Tanjim; Islam, Md. Jahidul (European Scientific Journal, ESJ, 2021)
This paper encompasses a state-of-the-art review on smart manufacturing system (SMS), focusing on theoretical relevance to technology development and technology management. The theoretical foundation of technology development has been reviewed based on the Rogers’ Diffusion of Innovation (DoI) theory and technology management has been focused on the basis of Technology Strategy Model (TSM) of Rieck and Dickson to shape the paper with theory of Management of Technology (MOT). A patent on SMS has been discussed to show how different technologies are integrated into this system. The characteristics of SMS have discussed the overall aspects of this future technological system. The the global textile complex has been depicted with a proposed SMS model of the apparel production unit. This study integrates the latest articles and technology on future manufacturing system perspectives, which gives a robust idea of mintegration have been identified as the major components of SMS. A brief model of SMS in the apparel production system demonstrated how SMS works in the industry level. The researchers on smart manufacturing can take away the above insights into their future research to take SMS research more forward.inimizing human interaction and maximizing the production efficiency in the manufacturing industry. The cyber-physical system, AI, ERP, digital twin, big data, additive manufacturing, cloud manufacturing, simulation, and vertical and horizontal